THE INFLUENCE OF ECONOMIC FACTORS ON THE DEVELOPMENT OF THE NATIONAL AUTOMOTIVE MARKET - T. Panova (Вестник университета)
The sales dynamic of new cars in Russia over the last ten years is presented. The stages of growth and decline of the automotive market are allocated. The economic factors influencing the development of the national automotive market are considered. The correlation of the automotive market and alterations in the Russian economy is tracked.